Computational Biology and Chemistry 2020
DOI: 10.5772/intechopen.89653
|View full text |Cite
|
Sign up to set email alerts
|

Search for Human-Specific Proteins Based on Availability Scores of Short Constituent Sequences: Identification of a WRWSH Protein in Human Testis

Abstract: Little is known about protein sequences unique in humans. Here, we performed alignment-free sequence comparisons based on the availability (frequency bias) of short constituent amino acid (aa) sequences (SCSs) in proteins to search for human-specific proteins. Focusing on 5-aa SCSs (pentats), exhaustive comparisons of availability scores among the human proteome and other nine mammalian proteomes in the nonredundant (nr) database identified a candidate protein containing WRWSH, here called FAM75, as human-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…To understand how the human immune system discriminates SARS-CoV-2 proteins (nonself) from its own proteins (self), we have been using the concept of short constituent sequences (SCSs) of amino acids in proteins [77][78][79][80][81][82][83]. The idea of information extraction from protein amino acid sequences based on SCSs is as old as Chou and Fasman (1974) [84] and Garnier et al (1978) [85].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand how the human immune system discriminates SARS-CoV-2 proteins (nonself) from its own proteins (self), we have been using the concept of short constituent sequences (SCSs) of amino acids in proteins [77][78][79][80][81][82][83]. The idea of information extraction from protein amino acid sequences based on SCSs is as old as Chou and Fasman (1974) [84] and Garnier et al (1978) [85].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ours, there are similar but independent approaches in the literature [86][87][88][89][90][91][92][93][94][95][96][97][98][99]. The number of amino acids in an SCS unit can vary, but we primarily use five amino acids (5-aa SCSs) [77][78][79][80][81][82][83]. The 5-aa window is technically convenient because there are only 20 5 combinations of 5-aa SCSs (also called pentats in our system but called pentapeptides or pentamers in others), which is not computationally demanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although protein analysis methods based on SCSs have been developed since 2005 [52][53][54][55][56][57][58], we introduced the self/nonself concept in SCS-based analysis for the first time in a previous study [59]. In that study, we showed that when using five amino acid stretches as SCS units, most SCSs in the SARS-CoV-2 proteome are self SCSs in reference to the human proteome [59].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, viral virulence may decrease. Although protein analysis methods based on SCSs have been developed since 2005 [27][28][29][30][31][32][33], we introduced the self/nonself concept in SCS-based analysis in a previous study for the first time [34]. In that study, we showed that when using 5 amino acid stretches as SCS units, most SCSs in the SARS-CoV-2 proteome are self SCSs in reference to the human proteome [34].…”
Section: Introductionmentioning
confidence: 99%